Cancer information needs according to cancer type: A content analysis of data from Japan's largest cancer information website - Tsuyoshi Okuhara (Preventive Medicine Reports, 2018)
The provision of information about cancer is an important aspect of cancer care. Cancer information provided online is expected to meet the needs of information seekers. Whether information needs vary according to tumor site is largely unknown. We aimed to examine similarities and differences in informational needs by cancer type. Data were collected using a questionnaire administered on Japan's largest cancer information website, “Ganjoho service”. A total of 2782 free descriptive responses in the period from April 2012 to December 2017 were analyzed using text-mining software. We identified the top 10 informational need contents, in order of appearance frequency, for eight tumor sites: gastric, colorectal, esophageal, lung, pancreatic, breast, cervical, and prostate cancer. Frequent information needs common to all tumor sites included symptoms, disease stages, treatments, chance of cure, recovery, metastasis, and recurrence. A need for information about diet, pain, side effects of treatments, complementary and alternative medicine was frequent for some tumor sites. Tumor site-specific information should include the following, according to cancer type: information of scirrhous carcinoma for gastric cancer; unusual feces for colorectal cancer; lung X-ray images for lung cancer; early detection for pancreatic cancer; adenocarcinoma, sexual activity, pregnancy, and childbirth for cervical cancer; breast conservation or reconstruction and triple negative cancer for breast cancer; test values and diagnosis and urinary problems for prostate cancer; and hormone therapy for breast and prostate cancer. Cancer information provided online should meet these frequent informational needs, considering similarities and differences of the information required according to tumor site. Keywords: Cancer, Neoplasms, Consumer health information, Information services, Information dissemination, Information seeking behavior, Cancer patients, Cancer survivors, Health communication